Pengaruh media edukasi gizi tentang indeks glikemik terhadap kadar glukosa darah pasien diabetes mellitus - Eliza, Eliza; Telisa, Imelda; Meilina, Ayu; Sumarman, Sumarman (Poltekkes Kemenkes Aceh, 2024)
Background: Diabetes Mellitus (DM) cases are increasing every year, IDF 2021 data shows DM cases aged 20-79 years with a total of 537 million people (10,5%), predicted to continue to increase in 2030 to 643 million people (11,3%) . DM sufferers can basically live a normal life if they follow four pillars, one of which is complying with education. It is important for patients to receive education in choosing foods that contain a low glycemic index because they are more slowly absorbed by the body into glucose, so that glucose levels in the body become more controlled. DM sufferers are advised to consume foods with a low glycemic index because these foods are more slowly absorbed by the body into glucose so that glucose levels in the body are more controlled. The more often DM patients receive education, the better their behavior, especially in choosing foods with a low glycemic index.Objectives: Knowing the effect of providing food glycemic index education on blood glucose levels in type 2 DM patients at Palembang Social Health Center.Methods: The research was carried out at the Palembang Social Health Center for 5 months, namely August to November 2021. Data was collected through measurements, namely body weight and height, interviews in the form of 3x24 hour recall and measurement of blood glucose levels. The type of research used is quantitative research using a Quasi Experimental research design. The research used a pretest and posttest with control group design with 46 respondents. The statistical analysis method used is the Paired T-test. The results of the dependent t-test between the treatment and comparison groups had a p value <0,05 which was equally significant, so it was continued with the independent t-test.Results: The results showed that there was a significant difference in blood glucose levels before and after providing counseling using posters (p=0,002) and booklets (p=0,004).Conclusion: Booklet media had more influence on increasing respondents' knowledge compared to using other media such as posters.